Interdisciplinarnost slovstvene folklore - Stanonik, Marija (ZRC SAZU, Založba ZRC, 2008)
The volume ('Interdisciplinarity of Literary Folklore') is divided into the following sections: Circumstances (with chapters: The spatial Aspect of Literary Folklore, The historical Aspect of Slovenian literary Folklore, The sociological Aspect of literary Folklore), The Man (with chapters: The anthropological Aspectof literary Folklore, The psychological Aspect of literary Folklore, The therapeutical Aspect of literary Folklore) and Supernality (with chapters: The mythological Aspect of literary Folklore, The theological Aspectof literary Folklore, The Art historical Aspect of literary Folklore). At the End is the suggest: Tales as Starting Points for local History Education.